SAARC facts and economic development - Rahman, M. L. (Mohammad Lutfur), 1933-; SARC Association, Bangladesh (Dhaka : SARC Association, Bangladesh, 1986)
History of South Asian Association for Regional Cooperation (SAARC), comprising Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka.
Bibliography: p. 200.
Keywords: South Asian Association for Regional Cooperation; South Asia -- Economic conditions